Pengaruh Csr, Financial Distress, dan Altman Z-Score terhadap Keputusan Dividen pada Perusahaan Otomotif yang Terdaftar di Bei Periode 2020 – 2025 - Sri Indri Oktavian; Heidi Siddiqa (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
The purpose of this study is to analyze the influence of Corporate Social Responsibility (CSR), Financial Distress, and Altman Z-Score on Dividend Decisions in automotive sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2025 period. This study is motivated by fluctuations in the Dividend Payout Ratio (DPR) in the automotive sector, which indicates changes in company dividend policy due to economic conditions, financial performance, and non-financial factors that influence management decision-making. The research method used is a quantitative approach with a causal associative research type to examine the relationship between the independent and dependent variables. The study population consists of automotive sector companies listed on the IDX, while the sample was determined using a purposive sampling technique based on certain criteria. Research data were obtained from annual reports and company financial statements for the 2020–2025 period. Data analysis was carried out using the Dividend Payout Ratio (DPR) as a proxy for dividend decisions and statistical testing to determine the effect of CSR, Financial Distress, and Altman Z-Score on company dividend, the data were processed using SPSS.